2018
DOI: 10.1186/s40557-018-0263-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of intestinal parasitic infections among asymptomatic food handlers working at Haramaya University cafeterias, eastern Ethiopia

Abstract: BackgroundIntestinal parasitic infections are major public health problems worldwide, with high prevalence in low income countries where substandard food hygiene practices are common. Asymptomatic food handlers with poor personal hygiene could be potential sources of parasitic infections. This study was aimed to assess the prevalence of intestinal parasitic infections and associated factors among asymptomatic food handlers working at Haramaya University cafeterias, eastern Ethiopia.MethodsA cross-sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
41
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(56 citation statements)
references
References 14 publications
14
41
1
Order By: Relevance
“…The highest prevalence of Entamoeba histolytica/ dispar in the current study may be attributed to widespread open field defecation, the resistance nature of cyst to chlorination, the survival of the cyst for several weeks in the environment and the cyst do not need development and maturation in the environment [43]. Also, most infected individuals are asymptomatic carriers, and they continue to shed eggs for a prolonged time [21].…”
Section: Hygienic Predictors Of Intestinal Parasites Among Food Handlersmentioning
confidence: 65%
See 1 more Smart Citation
“…The highest prevalence of Entamoeba histolytica/ dispar in the current study may be attributed to widespread open field defecation, the resistance nature of cyst to chlorination, the survival of the cyst for several weeks in the environment and the cyst do not need development and maturation in the environment [43]. Also, most infected individuals are asymptomatic carriers, and they continue to shed eggs for a prolonged time [21].…”
Section: Hygienic Predictors Of Intestinal Parasites Among Food Handlersmentioning
confidence: 65%
“…In Ethiopia, fragmented and dispersed studies conducted on the prevalence of intestinal parasitic infections among food handlers of food service establishments. The result of these studies showed variation and inconsistency in the prevalence of intestinal parasitic infections among food handlers: 10.9 to 45.3% in Ethiopian university cafeterias [15][16][17][18][19][20][21][22], 61.9% in prisons [14], 35% in orphanage centers [23], (32.3%) public hospitals [24], 14.5 to 44% in restaurants and cafeterias [13,[25][26][27][28]. According to the result of those studies, the prevalence of intestinal parasitic infections among food handlers of food service establishments was wide-ranging.…”
Section: Introductionmentioning
confidence: 99%
“…The lowest prevalence of IPIs among food handlers were reported in studies conducted in Wollo University student's cafeteria (15%) [11], Awi Amhara (14.75%) [23], and Aksum town, Tigray (14%) [12], whereas the highest prevalence (61.78%) was reported in a study conducted at East and West Gojjam public prison [10]. Seven of the studies were from Amhara region [10,11,[23][24][25][26][27], five from SNNP region [8,14,[28][29][30], three from Oromia region [9,13], one from Addis Ababa (7) and two from Tigray region [2,12]. However, there were no studies reported from Benishangul Gumuz, Harari and Gambela regions, and Dire Dawa.…”
Section: Characteristics Of Original Studiesmentioning
confidence: 99%
“…Studies in Ethiopia showed that the prevalence of intestinal parasitic infection among food handlers working at University student cafeteria's and public food establishment area such as Haramaya University cafeterias (14.3%) [9], East and West Gojjam prison (61.9%) [10], Wollo University student's cafeteria (15%) [11], Aksum Town (14.5%) [12], Jimma University Specialized Hospital (33%) [13], Addis Ababa University Students' Cafeteria (45.3%) [7], Hawassa University (20.6%) [14], and Mekelle University student's cafeteria (52.4%) [2]. However, the prevalence reflected in these small and fragmented studies varied widely and remained inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Ethiopia [19], Haramaya University [12] and at Prison, East and West Gojjam [5]. This might be due to the fact that those food handlers who didn't wash their hands with soap after toilet may infest with intestinal infection during eating, drinking and cooking.…”
Section: Discussionmentioning
confidence: 99%